2023
DOI: 10.1186/s12888-023-04953-z
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum copper, zinc, and selenium concentrations and depressive symptoms in the US adult population, NHANES (2011–2016)

Abstract: Background Evidence suggests that alterations in serum trace element concentrations are closely associated with mental illness. However, ​studies on the relationship between serum copper, zinc, and selenium concentrations and depressive symptoms are limited and with controversial results. We aimed to investigate the association between serum concentrations of these trace elements and depressive symptoms in US adults. Methods Data from the National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Data from the National Health and Nutrition Examination Survey further suggest a possible role for copper metabolism derangement in the development of depressive symptoms. From a total of 4552 individuals who are adult, Huang et al reported a significant association between higher serum copper concentrations and Patient Health Questionnaire-9 (PHQ-9)-defined depressive symptoms [ 116 ]. Higher peripheral copper has also been reported to be associated with a higher frequency of mild cognitive impairment, with a stronger association among individuals who are elderly and male [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data from the National Health and Nutrition Examination Survey further suggest a possible role for copper metabolism derangement in the development of depressive symptoms. From a total of 4552 individuals who are adult, Huang et al reported a significant association between higher serum copper concentrations and Patient Health Questionnaire-9 (PHQ-9)-defined depressive symptoms [ 116 ]. Higher peripheral copper has also been reported to be associated with a higher frequency of mild cognitive impairment, with a stronger association among individuals who are elderly and male [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
“…Depressed patients are more likely to exhibit inadequate zinc levels compared to healthy individuals, making zinc a potential biological marker for depressive disorders [ 23 , 24 ]. Several studies have supported the efficacy of zinc supplementation as an adjunct to antidepressant therapy [ 25 , 26 , 27 ]. Siwek et al .’s [ 28 ] study showed that zinc supplementation can help reduce depression scores and facilitate the treatment of patients resistant to antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is associated with the overproduction of ROS. Nevertheless, increased intracellular ROS caused by high oxysterol may alter cellular protein levels, trigger neuronal apoptosis, and activate inflammatory pathways in neurons [ 64 ]. Oxidative stress is an early event in the pathogenesis of AD [ 65 ].…”
Section: Hmgcr-mediated Neuroinflammationmentioning
confidence: 99%